Physical Fitness Component Profiles of Futsal Team Members of Universitas Padjadjaran in November 2011 - Raden Muhammad Tanri; Juliati Juliati; Vitriana Vitriana (Althea Medical Journal, 2015)
Background:  To be a good athlete, an athlete needs to possess good predominant components of physical fitness. Futsal Team of Universitas Padjadjaran has never won any competition. This study was conducted to identify the predominant component profiles of physical fitness of Futsal Team members of Universitas Padjadjaran. The predominant component profiles were classified based on the Indonesian National Sport Committee (KONI) standard.Methods: This study was carried out at the Faculty of Medicine Student Center of Universitas Padjadjaran in November 2012. Twenty two members of the Futsal Team were enrolled as subjects of the study. The study used the step test to examine aerobic endurance; the leg dynamometer to measure leg muscle strength; the squat jump test to test the leg muscle endurance; the vertical jump test to measure leg muscle power; and the sit and reach test to measure lower extremity flexibility. The data collected were analyzed using percentage.Results: Leg muscle strength was mostly in the fair category (95%). Leg muscle power was mostly in the good category (41%). Leg muscle endurance was mostly in the good category (82%). Leg flexibility was mostly in the excellent category (91%) and aerobic endurance was mostly in the good category (41%).Conclusions: Only several members of Universitas Padjadjaran Futsal Team have an excellent physical fitness profile. Most of the members fell into the fair and good category. DOI: 10.15850/amj.v2n3.524